2016
DOI: 10.1038/srep26315
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary potential and adaptation of Banksia attenuata (Proteaceae) to climate and fire regime in southwestern Australia, a global biodiversity hotspot

Abstract: Substantial climate changes are evident across Australia, with declining rainfall and rising temperature in conjunction with frequent fires. Considerable species loss and range contractions have been predicted; however, our understanding of how genetic variation may promote adaptation in response to climate change remains uncertain. Here we characterized candidate genes associated with rainfall gradients, temperatures, and fire intervals through environmental association analysis. We found that overall populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…An example of this is the fire regime adaptation of Banksia attenuata R.Br. (Proteaceae) in southwestern Australia, where candidate SNPs associated with rainfall and high temperature were diverse, whereas SNPs associated with specific fire intervals were mainly found in one allele (He & al., 2016). Multiple, independent dispersals from campo rupestre to cerrado has occurred in several distinct lineages, adding support to the notion that isolation by more severe fire regimes is readily overcome in Diplusodon.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is the fire regime adaptation of Banksia attenuata R.Br. (Proteaceae) in southwestern Australia, where candidate SNPs associated with rainfall and high temperature were diverse, whereas SNPs associated with specific fire intervals were mainly found in one allele (He & al., 2016). Multiple, independent dispersals from campo rupestre to cerrado has occurred in several distinct lineages, adding support to the notion that isolation by more severe fire regimes is readily overcome in Diplusodon.…”
Section: Discussionmentioning
confidence: 99%
“…At the mesic end of the rainfall gradient, fires are far less likely to reach the canopy (Cowling and Lamont ; Lamont et al ), and over the past 70 years (at least) tree‐crown‐reaching fires have occurred at an estimated 60–140‐year intervals (He et al ). This allows continuous growth of the main trunk, with trees recovering from fire through resprouting from the trunk and main branches rather than the base.…”
Section: Discussionmentioning
confidence: 99%
“…Fire has played a major role in shaping functional trait evolution in fire‐prone regions, globally (Keeley et al ; He and Lamont ), including southwestern Australia (SWA), for at least 80 million years (He et al , ; Lamont and He 2016). Following severe crown damage by fire, resprouting occurs through new shoot growth from surviving buds or meristems that are located aerially, basally or underground (Clarke et al ).…”
Section: Introductionmentioning
confidence: 99%
“…First, there must be genetic variation within the population that allows a physiologically beneficial response to low water availability. A study on adaptive genetic variation in response to rainfall and temperature in B. attenuata (usually co-occurring with species studied here) indicated that even populations occurring in wet habitats have genetic variation favouring survival under dry conditions [47]. However, directional selection could deplete population genetic variation, which limits the species' adaptive potential for other stresses that require different suites of genes and regulation networks.…”
Section: Discussionmentioning
confidence: 99%